2013
DOI: 10.2174/1874288220131127003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Lipid Profiles of Milk Bank Breast Milk and Infant Formulas

Abstract: Lipid profiles of seven human breast milk samples obtained from milk banks and four infant formulas were compared in view of the potential food hypersensitivities of certain infants to human milk.The cholesterol (0.15-0.26 mM) content of the human samples was about 50% lower than that found in the infant formulas whereas the triglyceride (TG, 173-386 mM) contents of these products were found to be comparable.The major saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA) were 16:0 and 18:1 respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…The percentage of fatty acids with hypercholesterolemic potential, corresponding to the sum of the lauric acid (C12: 0), myristic acid (C14: 0) and palmitic acid (C16: 0) fractions in the infant formulas analyzed, was in agreement with literature as well as with other infant formulas and human milk [1,27,37,39]. Saturated fat (C12:0, C14:0 and C16:0) raises the plasma cholesterol concentration, especially C14:0, whereas C18:0 has a neutral effect on cholesterol [1,41].…”
Section: Discussionsupporting
confidence: 88%
“…The percentage of fatty acids with hypercholesterolemic potential, corresponding to the sum of the lauric acid (C12: 0), myristic acid (C14: 0) and palmitic acid (C16: 0) fractions in the infant formulas analyzed, was in agreement with literature as well as with other infant formulas and human milk [1,27,37,39]. Saturated fat (C12:0, C14:0 and C16:0) raises the plasma cholesterol concentration, especially C14:0, whereas C18:0 has a neutral effect on cholesterol [1,41].…”
Section: Discussionsupporting
confidence: 88%
“…We found clear differences in lipidomic profiles by early feeding pattern, with differences in specific lipids across all main lipid classes between exclusively breast- and formula-fed infants. Notably, formula and breast milk are not dissimilar in their lipid composition, consisting primarily of TGs, 17,18 (with a larger diversity of fatty acids in the TGs of breast milk 19 ). Therefore, the infancy lipidomic profiles do appear to not only reflect the lipid composition of the milk intake, but also there may be additional effects of infant nutrition on early fat metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Authors investigating the cholesterol content of human milk reported a decrease of cholesterol concentration along lactation . In most of these studies, cholesterol content has been determined using colorimetric methods . Other approaches include GC with and without prior TLC separation, HPLC coupled to diode array detector and total reflectance Fourier transformed infrared (FTIR‐ATR) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%